2017
DOI: 10.3892/mmr.2017.7676
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cardiotrophin-1 overexpression is involved in the anti-fibrotic effect of Astrogaloside IV

Abstract: Astragaloside IV (AsIV), one of the major active ingredients in Astragalus membranaceus, has demonstrated remarkable antifibrotic effects via its antioxidative activity. Cardiac fibrosis is an important pathological mechanism during cardiac remodelling associated with heart failure. In the present study, the mechanism underlying the antifibrotic effect of AsIV upon isoprenaline (ISO) stimulation was investigated. AsIV significantly improved cardiac fibrosis in vivo and dose‑dependently inhibited ISO‑induced CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Also, relative heart weight was decreased by NAC supplementation. Similar results observed by Jia et al [66] who reported that cardiac broblast proliferation, collagen Ι and CT-1 overexpression induced by isoprenaline stimulation were effectively abrogated by NAC treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Also, relative heart weight was decreased by NAC supplementation. Similar results observed by Jia et al [66] who reported that cardiac broblast proliferation, collagen Ι and CT-1 overexpression induced by isoprenaline stimulation were effectively abrogated by NAC treatment.…”
Section: Discussionsupporting
confidence: 89%
“…It has been found that both increased ROS content and upregulated cardiotrophin 1 (CT1) expression, both of which were inhibited after the addition of astragaloside, which inhibited cardiac fibroblast proliferation and collagen production. 71 Inhibition of ROS-mediated MAPK activation can also inhibit myocardial fibrosis. AS-IV can significantly inhibit ISO-induced cardiac fibroblast proliferation and collagen I synthesis, reduce ROS levels, and inhibit the phosphorylation of extracellular signal-regulated kinase, p38MAPK, and cJun N-terminal kinase.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of experiments have confirmed that AR can effectively inhibit cardiovascular diseases such as myocardial ischemia-reperfusion injury [9], myocardial hypertrophy [58], vascular endothelial dysfunction [59], coronary heart disease [60], atherosclerosis [61], cardiac fibrosis [62] and viral myocarditis [63]. The main mechanisms of the treatment of cardiovascular diseases by AR and its main components are summarized in Figure 1.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Moreover, excessive ROS can promote the production of cardiotrophin-1 (CT-1), which can significantly promote cardiac fibrosis. AS-IV was also able to effectively inhibit isoproterenol-induced cardiac fibroblast proliferation and collagen production through negative regulation of ROS-mediated CT-1 upregulation [62] (Figure 1⑥).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%